2023
DOI: 10.3390/buildings13061433
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Behavior of Different Connections in Precast Concrete Shear Walls: Experimental and Analytical Investigations

Abstract: This study investigated the grouted sleeve splices and corrugated duct splices between shear walls and footing. In this regard, three shear walls were experimentally tested. One wall was cast monolithically with the foundation (RCWS), whereas two walls were precast. One wall was connected to the foundation using splice sleeves (PGWS), and another with corrugated duct splices (PCWS). All the walls were tested under reverse cyclic loading and a constant axial load. It was observed that the performance of specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Furthermore, precast structural systems have shown effective performance in withstanding earthquake loads [7][8][9][10]. The connection system in precast concrete construction is a critical aspect to ensure strength and ductility equivalent to monolithic concrete when subjected to earthquake loads [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, precast structural systems have shown effective performance in withstanding earthquake loads [7][8][9][10]. The connection system in precast concrete construction is a critical aspect to ensure strength and ductility equivalent to monolithic concrete when subjected to earthquake loads [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The method used to connect these components constitutes a central concern for precast shear wall systems. The reliability of the connection method is pivotal in establishing effective force transmission mechanisms and ensuring overall structural integrity [13][14][15][16]. A literature review indicates that the prevalent methods for connecting precast concrete shear wall systems presently encompass lap-spliced connection [17,18], post-tensioned connection [14,19,20], welded connection, bolted connection [16,21,22], and sleeve connection [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have proposed increasing the seismic performance and comfort of prefabricated structures by installing structural bracings and energy dissipation devices [26,27]. Previous research [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] has demonstrated that, given reliable design and construction practices, common methods for connecting precast concrete shear wall systems can achieve commendable seismic performance.…”
Section: Introductionmentioning
confidence: 99%